(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2025)
Effective personnel management is crucial for enhancing the economic efficiency of enterprises. This article explores mechanisms by which organizations can improve human resource management practices to boost productivity, profitability, and overall economic performance. Drawing on international best practices and theories from human resource management and organizational economics, we examine how performance-based incentives, digital HR systems, training programs, and leadership development contribute to economic efficiency. A literature review highlights foundational frameworks such as human capital theory and strategic HRM, linking investments in people to competitive advantage. We then discuss key management mechanisms and their impact on firm-level outcomes, supported by empirical evidence. A summary table is provided to encapsulate these mechanisms and their expected effects on economic efficiency. Finally, practical recommendations are offered for enterprises to implement these approaches, followed by conclusions emphasizing the strategic value of effective personnel management in today’s global business environment.